Antinociceptive Potential of Dichloromethane Extract of Rumex acetosa Leaf in Albino Rats - Stephen, Hyelda; Nakya, Faith Emmanuel; Sirante, Richard Martin (Darul Yasin Al Sys, 2024)
Rumex acetosa (Polygonaceae) is an ethnomedicinal herb and vegetable used to alleviate pain and inflammation. It is also commonly consumed as food. This study aimed to evaluate the antinociceptive effects of dichloromethane extracts from R. acetosa leaves using in vivo pharmacological models in albino rats. Dried leaf powder was extracted by maceration with dichloromethane (72 h). Acute oral toxicity was determined per OECD guidelines. Analgesic activity was assessed using tail immersion, hot plate (55°C) and acetic acid-induced writhing (0.7%) tests at doses of 50, 100 and 200 mg/kg body weight. Diclofenac sodium (25 mg/kg) served as reference drug. Phytochemical analysis was undertaken to screen major chemical classes. All doses of extract significantly (p<0.05) increased mean basal latency of tail withdrawal and hind paw licking by 46-162% and 63-207% respectively. Maximum analgesic effect comparable to diclofenac was observed at 200 mg/kg. In acetic acid model, extract exhibited marked (p<0.05) reduction in writhing frequency (55.49%) indicative of peripheral action. Preliminary phytochemical studies detected flavonoids, alkaloids, tannins and phenols as major compounds. R. acetosa leaf extracts displayed significant analgesic activity in vivo mediated via both central and peripheral pathways. The findings validate the traditional use of R. acetosa in pain management.